Enhancement Students’ Discussion Activity Through Student Teams Achievement Division (STAD) Co-operative Learning Models with Students’ Worksheet - Rohmadi, Tri; Dwiastuti, Sri; Rosyidi, Alvi (Universitas Sebelas Maret, 2013)
The purpose of this research to enhance students discussion activity by using of STAD (Student Teams Achievement Division) learning method with worksheets in class XI IPA 1 SMAN 5 Wonogiri 2008/2009 school year. Kind of this research is a classroom action research with the design consisted of two cycles and each cycle consists four stages includes planning, action, observation and reflection. The research subject was XI IPA 5 class students of SMAN 1 Wonogiri of 2008/2009 school year. Data collection carried out by observation, questionnaires and interviews. Analyzing data in this research is using qualitative analysis techniques, which refers to the interactive analysis model, consists of data reduction, data presentation and drawing conclusions. The validation of the data uses triangulation technique. The results of first cycle showed students discussion activity there has been an increased in but not optimized and continue in second cycle until the target of students discussion activity has been optimal reached. Based on the research it can be concluded application of the STAD (Student Teams Achievement Division) learning method with worksheets to improving student activity in the discussion, especially biology in class XI IPA 1 SMAN 5 Wonogiri 2008/2009 school year. Key Words: discussion activity, Student Teams Achievement Division